Exploring the Food Environment and household Gastronomy of low-income households - A Photovoice study - Samaddar, Arindam; Banerjee, Deep; Ynion, Jhoanne; Custodio, Marie Claire; Veetil, Prakashan Chellattan (International Rice Research Institute, 2023)
To meet the SDG of eradicating hunger and malnutrition by 2030, development of sustainable food and market systems has become a policy priority particularly for low- and middle-income countries such as India. Interventions promoting sustainable agriculture, small-scale farming, and equitable access to markets contribute to food and nutrition security, particularly for economically vulnerable groups. This study explored the factors that may influence food purchases by lowincome households in Nalanda, Bihar. Households were selected based on the multidimensional poverty index and geospatial habitat clustering. Participants’ interactions with the food environment was investigated using the photovoice approach, followed by exploratory interviews with male and female household members. The photo collages were coded according to the key elements of the food environment, while content analysis of the interviews was conducted based on the constructs of the socioecological model and the gastronomic systems research framework. Results showed that male household members are primarily responsible in engaging with the retail food environment where factors like availability, accessibility, and convenience influence their purchasing behavior. Females are responsible for addressing intrahousehold food needs and overseeing the household’s gastronomy (eating occasions, food pairing, ingredients, etc.) with traditions and sociocultural structures having an impact on how often they interact with markets. The decision to buy food is a calibrated equilibrium which results from the repetitive interaction of the household’s gastronomy and built food environment elements. Men and women may not have equal access to resources, but they possess distinct decision-making authorities.